PROCALCITONIN AS A NEW INFLAMMATORY MARKER IN ODONTOGENIC ABSCESSES OF HEAD AND NECK IN MALE POPULATION - Yanko Yankov; Yana Bocheva (Peytchinski Publishing, 2024)
Introduction: Procalcitonin (PCT) as a marker of inflammation has not been studied and analyzed in purulent inflammations of the head and neck of odontogenic origin, which is the aim of this original article. Materials and methods: This retrospective study includes 31 men with odontogenic abscesses of the head and neck with a mean age of 42 years. As a control group, 31 healthy men are used. In all of them, leukocytes (WBC), neutrophils (Neu), C-reactive protein (CRP), and procalcitonin (PCT) are tested. Results: The average values of the studied indicators in the patients are: CRP - 89.45±85.15 mg/l, WBC - 11.78±4.61x103/L, Neu - 8.79±4.58x103/L and PCT - 0.8±0.8 ng/ Jr. The average values of the same indicators in the control group are: CRP - 0.9±1.17 mg/l, WBC - 7.37±1.9x103/L, Neu - 4.13±1.43x103/L and PCT - 0.18±1.27 ng/ml. There is no positive correlation between PCT on the one hand and CRP, WBC and Neu on the other hand. Discussion: The mean values of CRP, WBC, Neu and PCT are higher in men with odontogenic abscesses compared to the healthy controls, and this is statistically significant. Although PCT does not correspond to WBC, Neu and CRP, it has a number of advantages over them - it increases its concentration only in infections of bacterial origin, it increases its levels earlier and reaches its highest concentration earlier, it has a longer half-life, and its level declines more rapidly after infections. Conclusions: All this suggests that PTC may soon become the most accurate marker in diagnosing, treating, and follow-up of patients with head and neck odontogenic abscesses.